The Rise of the Insumer: A Key Stakeholder of Crowdfunding - Kosch, Oskar (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2026)
Objective: Crowdfunding is a rapidly growing part of economy, with USD 8,003,935,277 being collected through the Kickstarter.com platform alone as of 11 May 2024. Crowdfunding platforms play an essential role in the contemporary crowdfunding process by bringing together two parties: project creators and project supporters, to fund projects. Relying on praxeological theory, this paper research objective is to explore a novel stakeholder type termed “insumer” (investing consumer), which comprises project supporters of crowdfunding.Research Design & Methods: Through a literature review, survey, archival search, and principles of taxonomy categorisation, the distinct nature of insumers as stakeholders is delineated.Findings: The analysis indicates that insumers constitute a distinct stakeholder type, characterised by their dual role as both investors and consumers. They engage in crowdfunding with expectations anchored in both material and non-material value exchanges, while also confronting inherent risks.Implications / Recommendations: Differentiating insumer as distinct stakeholder type should influence business model creation in crowdfunding, to comprise value flows and risk.Contribution: Recognising the significance of insumers as stakeholders in crowdfunding ventures, this study underscores their contribution to achieving success in crowdfunding campaign.